Ostrohrads'kyi Formalism for Singular Lagrangians with Higher Derivatives - Nesterenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We generalize the Ostrohrads'kyi method for the construction of the Hamiltonian description of a nondegenerate (regular) variational problem of arbitrary order to the case of degenerate (singular) Lagrangians. These Lagrangians are of major interest in the contemporary theory of elementary particles. For simplicity, we consider the Hamiltonization of a variational problem defined by a singular second-order Lagrangian. Generalizing the Ostrohrads'kyi method, we derive equations of motion in the phase space. We determine a complete collection of constraints of the theory.